1) 5^(x - 4) = 6^(x - 4) | : 6^(x - 4)
(5/6)^(x - 4) = 1
(5/6)^(x - 4) = (5/6)^0
x - 4 = 0
x = 4
2) 4^(x - 2)( 4² - 3) = 52
4^(x - 2)·13 = 52 | :13
4^(x - 2) = 4
x - 2 = 1
x = 3
3) сначала ОДЗ
2х² - 3х -1 > 0
D = 17
x1 = (3 + √17)/4
х2 = (3 - √17)/4
ОДЗ х∈(-∞; (3 - √17)/4) ∨((3 + √17)/4; + ∞)
Теперь решаем:
2х² - 3х -1 = 1
2х² - 3х - 2 = 0
D = 25
x1 = 2 ( входит в ОДЗ)
x2 = -1/2 ( входит в ОДЗ)
Ответ: 2; -1/2
4)log x= t
осн-е 2
3t² +2t - 5=0
решаем по чётному коэффициенту:
t = (-1 +-√1 + 15)/3 = (-1 +-4)/3
а) t1 = -5/3 log x = -4/3
осн-е 2
х = 2 ^ -4/3= 1/∛16
б) t2 = 1 log x = 1
осн-е 2
х = 2